Nutritional profiling of five New Zealand seaweeds – a preliminary assessment - Battershill, Zoe V. (Frontiers in Marine Science, 2024)
This study set out to provide a preliminary assessment of nutritional profiles of five selected New Zealand macroalgae to investigate the potential of land-cultivated Ulva spp. The New Zealand seaweeds species, selected from a limited range, were either collected from the wild (Pyropia plicata from Tauranga and Kaikōura), or were sourced from commercial wild harvest suppliers (Macrocystis pyrifera and Undaria pinnatifida), and were compared to land-based cultivated Ulva species (Ulva ralfsii and Ulva stenophylloides). Species were assessed for their content of crude protein, total lipids, carbohydrates, fibers, amino acids, mineral profiles, heavy metals and antioxidant capacity (Oxygen Radical Absorbance Capacity, ORAC). The two cultivated Ulva spp. had the highest crude protein content of the six seaweeds analyzed (approximately 21% dw, N×6.25), as expected with nutrient supplemented cultivation. They also had the highest total, essential and branched chain amino acid quantities (151, 70, and 29 mg/g for U. stenophylloides and 138, 62, and 27 mg/g for U. ralfsii). Though the two Ulva spp. were grown to the same cultivation specifications, they varied in carbohydrate and total fiber content (U. stenophylloides: 63% and 62%; U. ralfsii: 39% and 40%, respectively). Pyropia plicata collected in Kaikōura had the highest carbohydrate levels (65%) though not the highest total fiber. Both P. plicata had the highest trace minerals (417 mg/kg and 720 mg/kg for Kaikōura and Tauranga P. plicata respectively). All seaweeds analyzed showed no lipophilic antioxidants, though the two Phaeophyceae had the highest hydrophilic antioxidant content at 115 TE and 168 TE for Macrocystis pyrifera and Undaria pinnatifida, respectively. This paper provides a preliminary indication of the relative nutritional attributes of a range of potential New Zealand seaweed aquaculture targets benchmarked against sea-lettuce (Ulva spp.).